Automatic day-2 intervention by a multidisciplinary antimicrobial stewardship-team leads to multiple positive effects - Dik, Jan-Willem H.; Hendrix, Ron; Lo-Ten-Foe, Jerome R.; Wilting, Kasper R.; Panday, Prashant N.; van Gemert-Pijnen, Lisette E.; Leliveld, Annemarie M.; van der Palen, Job; Friedrich, Alex W.; Sinha, Bhanu (Frontiers in Microbiology, 2015)
Background: Antimicrobial resistance rates are increasing. This is, among others, caused by incorrect or inappropriate use of antimicrobials. To target this, a multidisciplinary Antimicrobial Stewardship-Team (A-Team) was implemented at the University Medical Center Groningen on a urology ward. Goal of this study is to evaluate the clinical effects of the case-audits done by this team, looking at length of stay (LOS) and antimicrobial use. Methods: Automatic e-mail alerts were sent after 48 hours of consecutive antimicrobial use triggering the case-audits, consisting of an A-Team member visiting the ward, discussing the patient’s therapy with the bed-side physician and together deciding on further treatment based on available diagnostics and guidelines. Clinical effects of the audits were evaluated through an Interrupted Time Series analysis and a retrospective historic cohort. Results: A significant systemic reduction of antimicrobial consumption for all patients on the ward, both with and without case-audits was observed. Furthermore, LOS for patients with case-audits who were admitted primarily due to infections decreased to 6.20 days (95% CI: 5.59-6.81) compared to the historic cohort (7.57 days; 95% CI: 6.92-8.21) (p=0.012). Antimicrobial consumption decreased for these patients from 8.17 DDD/patient (95% CI: 7.10-9.24) to 5.93 DDD/patient (95% CI: 5.02-6.83) (p=0.008). For patients with severe underlying diseases (e.g. cancer) these outcome measures remained unchanged. Conclusions: The evaluation showed a considerable positive impact. Antibiotic use of the whole ward was reduced, transcending the intervened patients. Furthermore, LOS and mean antimicrobial consumption for a subgroup was reduced, thereby improving patient care and potentially lowering resistance rates.